Public administration and the changing nature of space - Ventriss, Curtis (1994)
The importance of space has been largely ignored in the theory and practice of both public administration and public policy. This lack of theoretical interest in spatiality is somewhat surprising given that this concept raises salient policy and administrative issues in a global economic environment. It is argued that the changing nature of space poses new theoretical and practical challenges to the field, particularly in regards to what is referred to as the advent of spatial politics and how the need exists to integrate a more public notion of space and time into the analysis of public affairs. - Reproduced
Keywords: Public administration